(untitled) (Altre Modernità, 2025)
Published in 2010, Giorgio Vasta’s Spaesamento is a book that can be considered, in its own way, prophetic, capable as it is of fixing at its peak before its abrupt fall the socio-anthropological traits of a political and (sub)cultural era – ‘Berlusconism’ – that, at least officially, would conclude its 20-year historical parabola the next year, following the flare-up of the financial crisis and the subsequent turn of a technical government. Through several overlapping and interacting textual operations Vasta shapes a narrative co-implicating numerous epistemic stratifications, all underlying a dis-identitary quest that, gathered in a declared unity of time – 3 days – and space – Palermo –, takes on the cogent value of a ‘dispatriation’ in the homeland. The essay aims to dissect the different hermeneutic levels of Vasta’s narrative – existential quête, synecdotal coring of a numbed present, semiotic reading of the city by means of which to trace the symbolic phenomenology of the Berlusconi ‘ghost’ – first by isolating them to verify their tightness and then by interpreting them as they propose themselves in synchrony to better understand how they intersect, reacting to each other, within an autobiographical narrative destined to become naturaliter political narrative, radiography of a profound symbiotic disorientation – individual and collective –, lucid diagnosis of a ‘zero-sum’ country, affected by an acute ethical-moral ‘disease’.